2016
DOI: 10.1177/1479164115624680
|View full text |Cite
|
Sign up to set email alerts
|

Sensor and software use for the glycaemic management of insulin-treated type 1 and type 2 diabetes patients

Abstract: Lowering glucose levels, while avoiding hypoglycaemia, can be challenging in insulin-treated patients with diabetes. We evaluated the role of ambulatory glucose profile in optimising glycaemic control in this population. Insulin-treated patients with type 1 and type 2 diabetes were recruited into a prospective, multicentre, 100-day study and randomised to control (n = 28) or intervention (n = 59) groups. The intervention group used ambulatory glucose profile, generated by continuous glucose monitoring, to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 30 publications
1
33
1
Order By: Relevance
“…However, in contrast to Beck et al, the demonstrated HbA1c improvement was achieved without the use of alarms. Glycaemic benefit from real-time CGM use without alarms has been reported previously in type 2 diabetes [10].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…However, in contrast to Beck et al, the demonstrated HbA1c improvement was achieved without the use of alarms. Glycaemic benefit from real-time CGM use without alarms has been reported previously in type 2 diabetes [10].…”
Section: Discussionsupporting
confidence: 54%
“…There are some limitations including minimal characteristic and demographic data and other variables such as socio-economic status, education level, ethnicity, duration of diabetes, previous CGM use and the reason for use of the study device. However, usual exclusion criteria such as renal disease [10], planned dialysis [3] or recent myocardial infarction were also not applied, adding to the generalisability of the primary endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, we have lacked accurate measures of GV; CGM or FCGM now allow measurement of glucose levels 24 hours/day, which led to the development of a number of GV measures . Glycaemic coefficient of variation (CV) has been increasingly used as a simple yet reliable measure of GV and has shown correlations with diabetes complications . One difficulty with GV is the documented association with hypoglycaemia, making disentangling its direct role in diabetes complications problematic.…”
Section: The Role Of Glycaemia In Diabetes Complicationsmentioning
confidence: 99%
“…One difficulty with GV is the documented association with hypoglycaemia, making disentangling its direct role in diabetes complications problematic. Further CGM studies will provide more accurate and standardised information on GV, helping to fully understand the role of this glycaemic variable in diabetic vascular disease …”
Section: The Role Of Glycaemia In Diabetes Complicationsmentioning
confidence: 99%
See 1 more Smart Citation